The Relationship Between Convergent IGH Signatures and Severity of COVID-19 Patients by Next-Generation Sequencing of B-Cell Repertoire - Cai, Hongliu; Hu, Juan; Huang, Lingtong; Gao, Chunhua; Xu, Mi; Gao, Yuzhi; Sun, Tao; Fang, Xueling (Frontiers in Microbiology, 2022)
Object: To reveal convergent IGH signatures and the association with severity of COVID-19 patients. Method: 25 COVID-19 inpatients were classified into three clinical conditions: Mild, Severe, and Critical. We analyzed convergent IGH signatures by ImmuHub® BCR(B-cell receptor) profiling system. Result: IGH singleton frequency in patients is significantly lower than HDs(healthy donors). The clonality index of IGH in patients is significantly higher than HDs. Nevertheless, no significant difference was observed between the three groups. The difference in IGH clonality (top 5 clones) between post- and pre-treatment was significant in the improvement and deterioration groups. Three common public motifs were shared by all COVID-19 patients: ARDYGG, RWYFDY, and YYYYGMDV. Conclusion: B cells could recognize SARS-CoV-2 and produce clonal expansion. Patients who got better outcomes after treatment had higher IGH clonality. Three common public motifs - ARDYGG, RWYFDY, and YYYYGMDV, might be used for vaccine development. (ChiCTR2000029626)